Gambaran Sarana dan Prasarana Bimbingan dan Konseling pada Sekolah Menengah Negeri di Indonesia - Marimbun Marimbun; Rizky Andana Pohan (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2021)
The implementation of effective guidance and counselling services requires adequate facilities and infrastructure in accordance with national standards in Permendikbud No 111 of 2014 regarding guidance and counselling in secondary education in Indonesia. This study aims to describe the condition of the facilities and infrastructure for guidance and counselling in state secondary school; junior and senior state high school in Indonesia. The method used is the survey model. The research data were collected from 65 State Senior High Schools, 25 State Vocational High Schools and 58 State Junior High Schools spread over 71 districts/cities in 18 provinces in Indonesia. The instrument used a semi-open questionnaire adopted from Permendikbud No. 111 of 2014 regarding guidance and counselling in primary and secondary education. The results of the study showed as many as 4.68% of state senior high schools and 8.77% of state junior high schools did not have a counselling room. A total of 20.31% of state senior high schools, 58.82% of state vocational high schools, and 52.63% of state junior high schools did not have special room for individual counselling. A total of 10.93% of state high schools, 52.94% of state vocational high schools and 21.05% of state junior high schools did not have living room. A total of 39.06% of state senior high schools, 64.70% of state vocational high schools, and 64.91% of state junior high schools did not have group guidance and counselling rooms. A total of 31.25% of state senior high schools, 35.29% of state vocational high schools, and 59.64% of state junior high schools did not have data room. As many as 31.25% of state senior high schools, 82.35% of state vocational high schools, and 73.68% did not have library display room (bibliocounseling). This study revealed that the facilities and infrastructure for guidance and counseling in state secondary schools in Indonesia do not in accordance with the minimum standards issued in Permendikbud No. 111 of 2014. The implementation of effective and efficient guidance and counselling services requires facilities and infrastructure that corresponds with the minimum standards. Based on this study results, it is anticipated the stakeholders of guidance and counselling services, especially in education sections in Indonesia, would pay attention and provide the minimum standard of guidance and counselling facilities and infrastructure.